An efficient purification system for native minichromosome from Saccharomyces cerevisiae. - Unnikrishnan, A; Akiyoshi, B; Biggins, S; Tsukiyama, T (2012)
We have recently established a system for purifying minichromosomes in a native state from Saccharomyces cerevisiae. This system is extremely efficient, and a single-step purification yields samples with sufficient purity and quantity for mass spectrometry (MS) analysis of histones and non-histone proteins tightly associated with the minichromosome. The templates can also be used in various biochemical assays in vitro, such as transcription and recombination, and could be suitable for EM or other biophysical studies.